Integrated Practice Improvement Solutions—Practical Steps to Operating Room Management. (2nd September 2016) - Chernov, Mikhail; Pullockaran, Janet; Vick, Angela; Leyvi, Galina; Delphin, Ellise
ABSTRACT: Perioperative productivity is a vital concern for surgeons, anesthesiologists, and administrators as the OR is a major source of hospital elective admissions and revenue. Based on elements of existing Practice Improvement Methodologies (PIMs), "Integrated Practice Improvement Solutions" (IPIS) is a practical and simple solution incorporating aspects of multiple management approaches into a single open source framework to increase OR efficiency and productivity by better utilization of existing resources. Materials and Methods : OR efficiency was measured both before and after IPIS implementation using the total number of cases versus room utilization, OR/anesthesia revenue and staff overtime (OT) costs. Other parameters of efficiency, such as the first case on-time start and the turnover time (TOT) were measured in parallel. Results : IPIS implementation resulted in increased numbers of surgical procedures performed by an average of 10.7%, and OR and anesthesia revenue increases of 18.5% and 6.9%, respectively, with a simultaneous decrease in TOT (15%) and OT for anesthesia staff (26%). The number of perioperative adverse events was stable during the two-year study period which involved a total of 20, 378 patients. Conclusion : IPIS, an effective and flexible practice improvement model, was designed to quickly, significantly, and sustainably improve OR efficiency by better utilization of existing resources. Success of its implementation directly correlates with the involvement of and acceptance by the entire OR team and hospital administration.